Increased prevalence of MEFV exon 10 variants in Japanese patients with adult-onset Still's disease. (16th February 2015) - Nonaka, F; Migita, K; Jiuchi, Y; Shimizu, T; Umeda, M; Iwamoto, N; Fujikawa, K; Izumi, Y; Mizokami, A; Nakashima, M; Ueki, Y; Yasunami, M; et al.
Summary: Autoinflammatory diseases include a large spectrum of monogenic diseases, e.g. familial Mediterranean fever (FMF), as well as complex genetic trait diseases, e.g. adult-onset Still's disease (AOSD). In populations where FMF is common, an increased MEFV mutation rate is found in patients with rheumatic diseases. The aim of this study was to examine MEFV mutations in Japanese patients with AOSD. Genomic DNA was isolated from 49 AOSD patients and 105 healthy controls, and exons 1, 2, 3 and 10 of the MEFV gene genotyped by direct sequencing. MEFV mutation frequencies in AOSD patients were compared with controls. We found no significant difference in overall allele frequencies of MEFV variants between AOSD patients and controls. However, MEFV exon 10 variants (M694I and G632S) were significantly higher in AOSD patients than controls (6·1 versus 0%). In addition, there was no significant difference between MEFV variant carriers and non-carriers with clinical manifestations, but the monocyclic clinical course of the AOSD disease phenotype was observed less frequently in patients without MEFV variants. AOSD patients had significantly higher frequencies of MEFV exon 10 mutations, suggesting that low-frequency variants of MEFV gene may be one of the susceptibility factors of AOSD.